Cinnamon(Cinnamomum japonicum) subcritical water extract suppresses gut damage induced by dextran sodium sulfate in mouse colitis model. (December 2021) - Kim, Min Seo; Kim, Yong Dae; Kang, Seunghee; Kwon, Oran; Shin, Jae-Ho; Kim, Ji Yeon
Graphical abstract: Highlights: Clinical features and symptoms were improved in CSE-treated mice. CSE inhibited MPO activity and reduced colonic inflammation. CSE reduced pro-inflammatory reaction by inhibiting NF-κB inflammatory pathway. CSE altered the gut microbiome and increases alpha-diversity in mice. Abstract: Inflammatory bowel disease involves the breaking down of tight junctions and triggers leaky gut syndrome. In this study, we evaluated the effect of cinnamon subcritical water extract (CSE) on gut health improvement using a mouse colitis model induced by 5 % dextran sodium sulfate. The mice were treated with varying concentrations of CSE for 21 days and assessed. We examined histopathological changes, mRNA expression of cytokines and tight junction proteins, and alteration of the gut microbiome. CSE treatment improved clinical symptoms. Moreover, myeloperoxidase activity, interleukin (IL)-1β, IL-6, tumor necrosis factor-α protein, and mRNA expression were reduced in the CSE-treated groups. However, CSE increased the mRNA expression of tight junction proteins, such as ZO-1, occludin, mucin-1, mucin-2, and E-cadherin. In addition, CSE altered the microbiome to reduce inflammation. These results suggested that CSE could prevent dextran sodium sulfate sodium-induced colitis and disruption of the intestinal environment.